Narrative Landscape - Randolf T. Hester Jr. (Oz, 1988)
In addition to its utility, beauty, cleverness and cultural record, the design of the public landscape describes relationships of society to the natural environment and vice versa. The designed public landscape also expresses a dream, the embodiment of a vision of what society might be as well as what it is...